Hjelmkamera som opmærksomhedsunderstøttende teknologi. - Bøhm, Mikkel; Hagedorn-Rasmussen, Peter; Nickelsen, Niels Christian Mossfeldt (Psyke & Logos, 2016)
The application of a relatively simple technology in the form of a helmet-camera may support changes in awareness during and after an operative incidence. The helmet-camera is attached to the superior incident commander from the fire department. By way of the camera, it is possible to achieve further understanding of the operative effort, such as social interaction, ignorance and errors. In this article, recordings from a helmet-camera are analyzed by way of a dialogical session in relation to which the incident manager and the first author analyzes the incident manager’s awareness, participation and “struck” by way of dialogue characterized by reflection and reflexivity. The helmet-camera is analyzed as an awareness-technology, which embraces the potential to make a number of insecurities with regard to organizing principles visible, which the fire department uses during operative incidents. The delicacy in relation to the meeting between the incident manager and the team managers’ is striking. The article focuses on the critical situations and disturbances that stand in the way of a common understanding of the incidence effort.